DESCRIPTION OF THE LEVEL OF KNOWLEDGE OF THE ELDERLY ABOUT RHEUMATISM IN DALU SEPULUH A VILLAGE, TANJUNG MORAWA DISTRICT - Saragih, Tini Rezeki; Rahayu, Wika Sri; Andila, Fildzah Hassyati; Susanti, Nofi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Rheumatism is a chronic autoimmune disease that damages joints and the tissue around these joints. Rheumatism generally occurs in individuals over 55 years of age, and its prevalence increases with age. In Indonesia, rheumatism is one of the main health problems for the elderly. The aim of this research is to provide an overview of elderly knowledge about rheumatism in Dalu Sepuluh A Village, Tanjung Morawa District, identify factors that influence elderly knowledge about rheumatism, and provide recommendations for increasing elderly knowledge about rheumatism. The method used in this research is descriptive qualitative which provides an overview of the knowledge of elderly people regarding rheumatic diseases in Dalu Sepuluh A Village, Tanjung Morawa District. The research was conducted in April-May 2024 and it was found that the total elderly population in Dalu Sepuluh A village, Tanjung Morawa subdistrict was 465 elderly, and the sample used in this study was 10%, namely 47 elderly. The technique used to take samples from this population is a purposive sampling technique, namely collecting samples based on standards set by reviewers for the samples taken. The criteria for the sample were elderly people who were willing to be respondents, able to read, write and answer questions. The results of the researchers' findings showed that the majority of respondents' level of knowledge about rheumatism was sufficient, 28 respondents (60%), 11 respondents who had good knowledge (23%), and 8 respondents who had poor knowledge (17%).